2017
DOI: 10.14686/buefad.285744
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokullarda Bilişim Teknolojileri ve Yazılım Dersinin İşlenişi, Yaşanan Problemler ve Çözüm Önerileri: Öğretmen Görüşleri

Abstract: Öz: Bu çalışmanın amacı ortaokullarda Bilişim Teknolojileri ve Yazılım dersinin nasıl işlendiğini irdelemek ve bu derste yaşanan problemleri belirlemek olarak belirlenmiştir. Bu amaç doğrultusunda Türkiye'nin 31 farklı ilinde ortaokullarda görev yapan 50 bilişim teknolojileri öğretmeninden 2015-2016 yılının güz döneminde veri toplanmıştır. Karma araştırma yöntemi ile desenlenen bu araştırmada veri toplama aracı olarak araştırmacılar tarafından geliştirilen "demografik bilgi anketi" ve "bilişim teknolojileri de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
2
7
0
5
Order By: Relevance
“…The fact that all activities were not listed in the 2012 ITS curriculum and that the teacher's handbook and the textbook did not exist was among the most criticized topics by the teachers. This study finding was consistent with the results of other studies that scrutinized the 2012 ITS curriculum based on teacher views (Erçetin and Durak, 2017;Uzgur and Aykaç, 2016). Studies in the literature indicated that teachers considered the lack of teachers' handbook problematic and found the learning activities offered in the 2012 ITS curriculum unsatisfactory (Erçetin and Durak, 2017).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
See 4 more Smart Citations
“…The fact that all activities were not listed in the 2012 ITS curriculum and that the teacher's handbook and the textbook did not exist was among the most criticized topics by the teachers. This study finding was consistent with the results of other studies that scrutinized the 2012 ITS curriculum based on teacher views (Erçetin and Durak, 2017;Uzgur and Aykaç, 2016). Studies in the literature indicated that teachers considered the lack of teachers' handbook problematic and found the learning activities offered in the 2012 ITS curriculum unsatisfactory (Erçetin and Durak, 2017).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
“…This study finding was consistent with the results of other studies that scrutinized the 2012 ITS curriculum based on teacher views (Erçetin and Durak, 2017;Uzgur and Aykaç, 2016). Studies in the literature indicated that teachers considered the lack of teachers' handbook problematic and found the learning activities offered in the 2012 ITS curriculum unsatisfactory (Erçetin and Durak, 2017). It can be stated that the teachers considered the lack of learning activities in previous ITS curricula as unsatisfactory as well (Tanataş, 2015).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
See 3 more Smart Citations